Transposing Continuance and Normative Organizational Commitment to Affective Commitment among Pharmaceutical Executives: Mediating Role of Herzberg’s Hygiene-Motivation Factors - Theophilus Ehidiamen OAMEN; Maduabuchi Romanus IHEKORONYE (Journal of Human Resource Management)
Purpose—Employee Organizational Commitment (OC) is a critical asset for any organization as it guarantees enduring job satisfaction, reduced turnover intention, and purposeful attainment of organizational objectives. Although affective commitment (OCA) is the most desirable domain compared to continuance (OCC) and normative commitment (OCN), linkages between the domains have not been empirically tested through the lens of Herzberg’s hygiene-motivation theory and the three-compartment model of organizational commitment. Aim(s) - The study explored the mediating influence of hygiene and motivation factors on the relationship between OCN, OCC, and OCA. Design/methodology/approach- An online questionnaire-based cross-sectional survey of 369 randomly selected pharmaceutical marketing executives from 30 indigenous and multinational pharmaceutical marketing companies in Nigeria. OCN and OCC were operationalized as independent variables, hygiene and motivation factors as mediators, while OCA was the main dependent variable. Covariance-based structural equation modeling and ANOVA techniques were used to develop and test hypotheses. Findings— The results revealed low and non-significant correlations between OCN and OCC. Participants perceived OCA as more desirable compared to OCC and OCN. The direct effect of OCN on OCA compared to OCC was positive and significant. From the study results, the direct effects of OCN on hygiene, motivator factors, and OCA were positive and significant (hypotheses fully supported) while the direct effects of OCC were negative and non-significant (partially supported). Hygiene and motivator factors mediated the effects of OCN on OCA, unlike OCC. The study’s findings showed that hygiene and motivators were partial mediators for OCN to OCA. Interestingly, the mediating effect of the motivator factor from OCN to OCA was negative. OCN behavior positively transposed to the desired behavior-OCA when hygiene factors are optimal for employees. Limitations of the study- The study primarily focussed on the pharmaceutical marketing sector; hence, it should be replicated in other healthcare sectors. Practical implications- Managers should routinely evaluate employee dissatisfiers (hygiene factors) and satisfiers (motivator factors) to identify key improvement areas for individual and organizational benefit. Originality/value- The study adds to the literature on OC by expounding the facilitating role of Herzberg factors to stimulate desired behavioral change underlying employee commitment in the workplace.